2022
DOI: 10.3889/oamjms.2022.8495
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Flipped Classroom during the COVID-19 Pandemic in Higher Pharmaceutical Education

Abstract: BACKGROUND: Despite the apparent advantages of the flipped classroom model especially during a pandemic or natural or technogenic disasters, its overall effectiveness in higher medical and pharmaceutical education continues to be debated. AIM: The goal of the study was to test the effectiveness and acceptability of using the flipped classroom model during the COVID-19 pandemic in higher pharmaceutical education based on the example of the “Pharmaceutical Marketing” discipline at Sechenov First Moscow State M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Maintenance of students' good performances as well as good students' engagement in the learning process have been also described all over the world in studies reporting online inverted classes as a pedagogical model during COVID-19 lockdowns or other contexts and related to different CUs comprising human health topics ( Banks and Kay, 2022 , Divjak et al, 2022 , Hew and Lo, 2018 , Ji et al, 2022 , Litvinova et al, 2022 ). Specifically, in the Microbiology and/or Food Science teaching, Salter and Gardner (2016) concluded that the combination of online inverted classes and face-to-face classes was the students' preference, promoting a variety of learning experiences and catered for a range of learning styles.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Maintenance of students' good performances as well as good students' engagement in the learning process have been also described all over the world in studies reporting online inverted classes as a pedagogical model during COVID-19 lockdowns or other contexts and related to different CUs comprising human health topics ( Banks and Kay, 2022 , Divjak et al, 2022 , Hew and Lo, 2018 , Ji et al, 2022 , Litvinova et al, 2022 ). Specifically, in the Microbiology and/or Food Science teaching, Salter and Gardner (2016) concluded that the combination of online inverted classes and face-to-face classes was the students' preference, promoting a variety of learning experiences and catered for a range of learning styles.…”
Section: Discussionmentioning
confidence: 95%
“…Although there are several reports on online laboratory classes for diverse scientific areas ( Banks and Kay, 2022 , Cormier and Voisard, 2018 , Divjak et al, 2022 , Hew and Lo, 2018 , Ji et al, 2022 , Litvinova et al, 2022 , Mshayisa and Basitere, 2021 , Salter and Gardner, 2016 ), information on the application of inverted classes to the teaching of Food Microbiology for undergraduate students is unknown. Here, we described the use of inverted classes in the laboratory teaching of Food Microbiology CUs taught to PSIMD and NSFD students of University of Porto during a semester comprising online and face-to-face classes due to on/off COVID-19 lockdown periods.…”
Section: Introductionmentioning
confidence: 99%